2016
DOI: 10.1002/etc.3389
|View full text |Cite
|
Sign up to set email alerts
|

Barley root hair growth and morphology in soil, sand, and water solution media and relationship with nickel toxicity

Abstract: Barley, Hordeum vulgare (Doyce), was grown in the 3 media of soil, hydroponic sand solution (sand), and hydroponic water solution (water) culture at the same environmental conditions for 4 d. Barley roots were scanned, and root morphology was analyzed. Plants grown in the 3 media had different root morphology and nickel (Ni) toxicity response. Root elongations and total root lengths followed the sequence soil > sand > water. Plants grown in water culture were more sensitive to Ni toxicity and had greater root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Rice shows different responses to aerobic and flooding conditions, and P uptake in particular was reported to be greater in aerobic conditions than in flooded conditions (Wissuwa and Ae, 2001b). Sand culture rather than water culture was also recommended to estimate nickel toxicity in barley roots (Lin et al, 2016). We did not use any aeration, and this may be one of the reasons H did not work in ambient conditions even though the medium was replaced every 4 d. The HS method can be performed in ambient conditions, and in our experiments it saved 70% of the nutrient medium compared with hydroponics in the H experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Rice shows different responses to aerobic and flooding conditions, and P uptake in particular was reported to be greater in aerobic conditions than in flooded conditions (Wissuwa and Ae, 2001b). Sand culture rather than water culture was also recommended to estimate nickel toxicity in barley roots (Lin et al, 2016). We did not use any aeration, and this may be one of the reasons H did not work in ambient conditions even though the medium was replaced every 4 d. The HS method can be performed in ambient conditions, and in our experiments it saved 70% of the nutrient medium compared with hydroponics in the H experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The largest difference between the 2 culture media was that the EC50 from the hydroponic bioassay was roughly 10 times lower than that from the sand culture, suggesting greater sensitivity of wheat root elongation to Ni 2þ toxicity in hydroponic culture. Our results showed that toxicity models developed from sand culture better predicted toxicity than those from hydroponic culture, presumably attributable to structural differences between the 2 media [11]. However, it should also be noted that the water in hydroponic experiments was changed every 48 h, whereas in sand and soil culture it was not renewed.…”
Section: Differential Effects Of the Culture Mediamentioning
confidence: 69%
“…By increasing the root surface area, root hairs enhance metal uptake and therefore metal toxicity [48]. Accordingly, sand culture offers a medium that is structurally similar to that of soils, and the EC50 obtained in sand culture was close to that obtained from the soil tests [11]. This would explain the better performance of the models based on the sand than on the water cultures.…”
Section: Differential Effects Of the Culture Mediamentioning
confidence: 75%
See 1 more Smart Citation
“…Soil is not a solution, it is a complex matrix of particles, liquid, and air pockets (Robbins and Dinneny, 2015). Roots develop and respond differently in soil than in liquid media due to the difference in solute diffusion, mechanical impedance, and the gas exchange properties of liquid versus soil (Gahoonia and Nielsen, 1997; Genc et al, 2007; Chapman et al, 2011; Rich and Watt, 2013; Robbins and Dinneny, 2015; Lin et al, 2016). The use of PEG to simulate water deficits in soil has generally been avoided as PEG concentration and accessibility changes as the soil dries, but the use of PEG in a solid-matrix such as soil is viable when used in a non-transpiring system where the soil saturation levels remain constant.…”
Section: Introductionmentioning
confidence: 99%